2020
DOI: 10.1038/s41612-020-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Linking midlatitudes eddy heat flux trends and polar amplification

Abstract: Eddy heat fluxes play the important role of transferring heat from low to high latitudes, thus affecting midlatitude climate. The recent and projected polar warming, and its effects on the meridional temperature gradients, suggests a possible weakening of eddy heat fluxes. We here examine this question in reanalyses and state-of-the-art global climate models. In the Northern Hemisphere we find that the eddy heat flux has robustly weakened over the last four decades. We further show that this weakening emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 69 publications
(79 reference statements)
2
34
0
Order By: Relevance
“…TOMS, OMI, and OMPS. Furthermore, both de Laat et al (2017) and Tully et al (2019) appear not to have homogenized the different data sets used and did not infer missing measurements during the polar night and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TOMS, OMI, and OMPS. Furthermore, both de Laat et al (2017) and Tully et al (2019) appear not to have homogenized the different data sets used and did not infer missing measurements during the polar night and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Interannual variability in Antarctic stratospheric dynamics, manifest most obviously in interannual variability in Antarctic stratospheric temperatures, drives significant interannual variability in the severity of Antarctic ozone depletion (Schoeberl et al, 1996;Newman and Nash , 2000;Newman et al, 2004Newman et al, , 2006. Using TCO measurements from multiple satellite-based instruments, and after accounting for interannual variability in stratospheric temperatures, de Laat et al (2017) found that ozone mass deficit decreased by 0.77 ± 0.17 Mt yr −1 (2σ ) between 2000 and 2015. More recently, Tully et al (2019) analysed linear trends in several Antarctic ozone hole metrics over the periods 1979 to 2001 and 2001 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the attendant stratospheric circulation anomalies can propagate downward to the tropopause, with the stratospheric forcing subsequently able to alter tropospheric SAM by changing the synoptic-scale eddy feedbacks that maintain variations in the polar front jet (Christiansen, 1999(Christiansen, , 2001Kodera and Kuroda, 2002;Limpasuvan et al, 2004;Song and Robinson, 2004;Smith and Scott, 2016). Consequently, a number of studies have suggested that the circulation changes induced by the ozone hole involve alterations to these dynamical processes, although the exact mechanisms remain uncertain (e.g., Hartmann et al, 2000;Chen and Held, 2007;McLandress et al, 2010McLandress et al, , 2011Harnik et al, 2011;Orr et al, 2012Orr et al, , 2013Hu et al, 2015). Orr et al (2012) performed a model-based study focused on a momentum budget analysis within the transformed Eulerian mean (TEM) framework.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric reanalysis datasets combine observations with a fixed weather forecast model in an optimal way to construct a best estimate of the state of the atmosphere. They have previously been used to investigate the circulation trends in the stratosphere and troposphere that occur in response to the ozone hole (e.g., Chen and Held, 2007;Harnik et al, 2011;Shaw et al, 2011;Orr et al, 2012Orr et al, , 2013Banerjee et al, 2020). These studies tend to be based on a single reanalysis dataset, despite many others being available .…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps especially an issue in the stratosphere, as compared to the troposphere this region is characterised by smaller volumes of observational data available for assimilation and larger biases in observational data , implying a greater reliance on the performance of the forecast model and its representation of dynamical processes (e.g., Orr et al, 2010). The representation of the underlying dynamics in reanalyses is therefore an additional concern, which has not been examined for the SH despite showing nonnegligible differences for some diagnostics in the Northern Hemisphere (e.g., Bengtsson et al, 2006;Lu et al, 2015;Martineau et al, 2016Martineau et al, , 2018bChemke and Polvani, 2020).…”
Section: Introductionmentioning
confidence: 99%